Antibacterial and disinfecting effects of standardised tea extracts on more than 100 clinical isolates of methicillin-resistant Staphylococcus aureus - Feilcke, Ruth; Bär, Volker; Wendt, Constanze; Imming, Peter (Plants, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) infections are still a major problem in hospitals. The excellent safety profile, accessibility and anti-infective activity of tea extracts make them promising agents for the treatment of infected wounds. To investigate the possibility of sterilising MRSA-infected surfaces, including skin with tea extracts, we determined the MICs for different extracts from green and black tea (Camellia sinensis), including epigallocatechin gallate (EGCG), on a large number of clinical isolates of MRSA, selected to represent a high genetic diversity. The extracts were prepared to achieve the maximal extraction of EGCG from tea and were used as stable lyophilisate with a defined EGCG content. All extracts showed a complete inhibition of cell growth at a concentration of approx. 80 µg/mL of EGCG after a contact time of 24 h. Time-kill plots were recorded for the extract with the highest amount of EGCG. The reduction factor (RF) was 5 after a contact time of 240 min. EGCG and tea extracts showed an RF of 2 in methicillin-sensitive S. aureus. Extracts from green and black tea showed lower MICs than an aqueous solution with the same concentration of pure EGCG. To the best of our knowledge, we are the first to show a reduction of 99.999% of clinically isolated MRSA by green tea extract within 4 h.
Gesehen am 19.01.2024